2001
DOI: 10.1016/s0014-5793(01)02815-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipemia: a role in regulating UCP3 gene expression in skeletal muscle during cancer cachexia?

Abstract: Rats bearing the Yoshida AH-130 ascites hepatoma showed an increased expression of both uncoupling protein-2 (UCP2) (two-fold) and UCP3 (three-to four-fold) in skeletal muscle (both soleus and gastrocnemius). The increase in mRNA content was associated with increased circulating concentrations of fatty acids (two-fold), triglyceride (two-fold) and cholesterol (1.9-fold). Administration of nicotinic acid to tumor-bearing rats abolishes the hyperlipidemic increase associated with tumor burden. The vitamin treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 63 publications
0
20
1
Order By: Relevance
“…In previous work carried out in our laboratory, using the Yoshida AH-130 ascites hepatoma as a cachexia model in the rat, we have reported that both UCP2 and UCP3 gene expressions are increased in skeletal muscle [19], and that TNF seems to be partly responsible for the activation of the transcription of the two genes [38] via an increased FFA plasma concentration [20]. Thus, we have shown that the administration of nicotinic acid (a hypolipidemic agent) resulted in a downregulation of the UCP3 gene in soleus muscle, while no changes were observed concerning UCP2 mRNA content, suggesting a differential regulation of the UCP3 gene versus the UCP2 one, since only the former responded to variation in circulating FFA levels [20]. The results presented here question the fact that increased UCP3 gene expression in skeletal muscle is invariably associated with an elevation of circulating FFA, as mentioned before.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous work carried out in our laboratory, using the Yoshida AH-130 ascites hepatoma as a cachexia model in the rat, we have reported that both UCP2 and UCP3 gene expressions are increased in skeletal muscle [19], and that TNF seems to be partly responsible for the activation of the transcription of the two genes [38] via an increased FFA plasma concentration [20]. Thus, we have shown that the administration of nicotinic acid (a hypolipidemic agent) resulted in a downregulation of the UCP3 gene in soleus muscle, while no changes were observed concerning UCP2 mRNA content, suggesting a differential regulation of the UCP3 gene versus the UCP2 one, since only the former responded to variation in circulating FFA levels [20]. The results presented here question the fact that increased UCP3 gene expression in skeletal muscle is invariably associated with an elevation of circulating FFA, as mentioned before.…”
Section: Resultsmentioning
confidence: 92%
“…In fact, it has been speculated that UCP3 could have a role in lipid metabolism, possibly as a mitochondrial fatty acid carrier [35], although some controversy still exists [36]. On these lines, different experiments have shown that when the circulating FFA concentration is decreased, by means of hypolipidemic agents, the induction in both UCP2 and UCP3 is abolished [10,20]. In addition, the presence of fatty acids in C2C12 myotube cultures results in an increase in UCP3 gene expression [37].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for the increase in levels in skeletal muscle is complex. In a rat model of cachexia, the increase in UCP was associated with a twofold increase in circulatory fatty acid, and reduction of hyperlipidemia with nicotinic acid also reduced UCP3 expression in soleus but not in gastrocnemius muscles (31). However, in a murine model of cachexia, the increased UCP2 and UCP3 gene expression in skeletal muscle was not linked to a rise in circulatory fatty acids (30).…”
Section: Energy Expenditurementioning
confidence: 90%
“…Thus, systemic administration of TNF to rats results in an increase in both UCP2 and UCP3 gene expression in skeletal muscle [12]. This does not seem to be the result of a direct effect of the cytokine but rather seems to be associated with the hyperlipemia induced by TNF administration [47]. In fact, Masaki et al have demonstrated that TNF regulates the in vivo expression of the UCP family differentially and tissue dependently [48].…”
Section: Oxidative Phosphorylation Uncoupling: Ucpsmentioning
confidence: 97%